Accumulation of nickel in Rubiaceae Hyperaccumulator plant in Kinabalu National Park, Sabah / Muhammad Irfan Rifnur Ariffin - Ariffin, Muhammad Irfan Rifnur (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2019)
The ultramafic soil is fundamental element in producing hyperaccumulator plant due to its high metal concentration. The Rubiaceae family is well distributed over ultramafic soil has a very high potential recognize as a hyperaccumulator plant. Thus, the hyperaccumulator plant is very useful in phytomining technology because their ability to accumulate metal and live in the high metal concentration soil. This green technology was established because has potential to replace conventional mining hence reducing the pollution caused by conventional mining. Nickel is one of the valuable metal among other metal. Therefore, nickel hyperaccumulator plant is promising in phytomining technology. The use of portable X-Ray Fluorescence was fully utilized to scan the plant specimen and determine its metal concentration without destructing the specimen. Thus, scanning of the her barium specimen is very efficient to find potential hyperaccumulator plants. A total of 2556 Rubiaceae herbarium plant specimens in Kinabalu Park, Sabah was scanned and found that Psychotria sarmentosa and Urophylum sp. are nickel hyperaccumulator plants. This is a new report of Urophylum sp. as a new nickel and cobalt hyperaccumulator plant. Moreover, the three samples of fresh Psychotria sarmentosa was collected at Mount Tombuyukon to determine its nickel concentration in different plant parts and leaf size. It is found that, Psychotria sarmentosa accumulate most of the nickel in its leaf (50567.29 ± I 042.22 ppm) and middle range size of leaf (34.04cm < L < 51.11cm) has most nickel (37269.86 ± 923.06 ppm) than other sizes. Therefore, two species of Rubiaceae from Kinabalu National Park are hyperaccumulators. The nickel is concentrated on the middle size leaf. However, further research is eminent to authenticate and to determine their potential in phytomining.